Contributions to the knowledge of amphipod fauna (Crustacea, Amphipoda) from the Danube Delta, Romania - Ana-Maria PURCARI; Mirela CÎMPEAN; Karina Paula BATTES (Studia Universitatis Babeș-Bolyai. Biologia, 2020)
The amphipod species Pontogammarus maeoticus (Sovinskij, 1894) was identified in two locations from the Danube Delta, Romania (Sfântu Gheorghe and Sulina beaches) in July 2019. This is an eurybiont species, able to withstand high salinity variations characteristic to mixing fresh and sea waters. The individuals presented a special character in their morphology, a depression on the basis of pereiopod V. The present paper contributes to the knowledge of existing amphipod fauna from the Danube Delta, in the Black Sea coast area.